Reliability analysis of support strategies in tunnel construction: Insights from geomechanical analysis of jointed rock masses - Naeem Abbas; Kegang Li; Yewuhalashet Fissha; Jitendra Khatti; Merhawi Berhe Geberegergis; N.Rao Cheepurupalli; Blessing Olamide Taiwo; Zemicael Gebrehiwot; Yemane Kide; N. Sri Chandrahas (Results in Earth Sciences)
In this study, the dynamics of jointed rock masses in the challenging geological setting of the Himalayas, with a focus on tunneling activities and recommendations of support for jointing rock mass, were investigated. The jointing in Himalayan rocks mass poses significant implications for tunnel stability, demanding a detailed analysis of joint characteristics, such as joint connectivity and spacing. The parameter of joint connectivity rate along the Himalayas becomes a key focus, impacting rock mass strength for tunneling. The study utilized quadratic polynomial and reciprocal expressions of power functions, to characterize the nonlinear variation of jointed rock mass strength concerning joint connectivity rate. Integration of these results leads to unified equations that consider rock type dependence, having a realistic representation of jointed rock behavior. Numerical analysis reveals that jointing in rock affects instability through complex stress regimes, identifying critical stress concentration points. The effectiveness of support measures like rock bolts and shotcrete are validated, demonstrating their role in reducing displacements in tunnels.